ANALISIS IMPLEMENTASI KEBIJAKAN PAJAK PERTAMBAHAN NILAI ATAS TRANSAKSI E-COMMERCE DALAM MENINGKATKAN POTENSI PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA JAKARTA PASAR REBO TAHUN 2023 - Hamidah, Prita; Ramdan, Alief (Jurnal Ilmu Administrasi Publik, 2024)
Internet technology is changing the global economy through e-commerce, including distribution, purchasing, delling and marketing of services. The growth of online commerce has an impact on increasing the number of e- commerce business actors and e-commerce transactions that exceed conventional traders. With the increasing number of taxpayers, it a also important to ensure compliance and awareness of their tax obligations. This research aims to analyze the implementation of the Value Added Tax (VAT) policy on e-commerce transactions, as well as identify the factors inhibiting and driving the implementation of the VAT policy to increase the potential for tax revenue at KPP Pratama Jakarta Pasar Rebo in 2023. Using qualitative research methods, namely using techniques data collection through interviews, observation and documentation. The research results show that the implementation of e-commerce transaction policies at KPP Pratama Jakarta Pasar Rebo is quite good in terms of resources. However, communication between officers and taxpayers is still lacking and taxpayers do not fully understand the policy. Inhibiting factors include low taxpayer awareness, lack of knowledge and understanding, and minimal supervision from tax officers. Driving factors include collaboration with e-commerce platforms to carry out outreach and persuasive approaches to taxpayers to increase tax awareness and compliance, which ultimately increases tax revenues.